Carotid–Femoral Pulse Wave Velocity as a Biomarker of Arterial Stiffness and Exercise-Induced Cardiovascular Adaptation in Athletes: A PRISMA-Based Review and Mexican Consensus Proposal - Rivera Cisneros, Antonio Eugenio; Morales Corral , Pedro Gualberto; Morales Elizondo , Dulce Edith; Montaño Corona , Guadalupe; Melchor Moreno, Teresa; Sánchez González , Jorge Manuel (Horizonte Académico, 2026)
Background: Pulse wave velocity (PWV) is the most robust non-invasive marker of arterial stiffness and an independent predictor of cardiovascular events. Objective: To analyze associations between PWV and hemodynamic, hematological, and metabolic variables, and to synthesize evidence through a PRISMA-based systematic review to inform a practical consensus applicable to Mexico. Methods: Observational, analytical framework integrated with a PRISMA 2020 systematic review of randomized trials and meta-analyses on exercise and PWV. Results: PWV was significantly associated with mean arterial pressure, LDL-C, triglycerides, glucose, and hematocrit. Aerobic exercise consistently reduced PWV (−0.6 to −1.3 m/s), whereas high-intensity resistance training showed neutral or adverse effects depending on baseline stiffness. Conclusions: PWV should be systematically incorporated into cardiovascular evaluation of athletes, stratified by training modality. This PRISMA-based review summarizes evidence on cfPWV in athletes and proposes consensus recommendations for Mexico.